Impact of COVID-19 pandemic on older cancer patients: Proposed solution by the International Geriatric Radiotherapy Group - Nguyen, Nam Phong; Karlsson, Ulf Lennart; Lehrman, David; Mazibuko, Thandeka; Saghatelyan, Tatul; Thariat, Juliette; Baumert, Brigitta G.; Vinh-Hung, Vincent; Gorobets, Olena; Giap, Huan; Singh, Sankalp; Chi, Alexander; et al. (Frontiers in Oncology, 2023)
Older cancer patients are disproportionally affected by the Coronavirus 19 (COVID-19) pandemic. A higher rate of death and potential long-term disability produce fear of contracting the virus. Delay in diagnosis and treatment may lead to a poor outcome which may be prevented. Thus, physicians should devise a policy which help older patients overcome their fear to seek early cancer diagnosis and treatment and to support their need during treatment. A combination of telemedicine and holistic approach involving prayers for older cancer patients with a high level of spirituality may improve vaccination rates and improve their quality of life during treatment. Collaboration between health care workers, social workers, faith-based leaders, and cancer survivors may be crucial to achieve that goal. Social media may be an important component to portray a positive message for older cancer patients that chronological age is not an impediment to treatment.